Primal leadership realizing the power of emotional intelligence - Goleman, Daniel (New York Audio Renaissance, 2002)
Daniel Goleman's international bestseller "Emotional Intelligence" forever changed our concept of "being smart," showing how emotional intelligence (EI) - how we handle ourselves and our relationships - can determine life success more than IQ. Then, "Working with Emotional Intelligence" revealed how stellar career performance also depends on EI. Now, Goleman teams with renowned EI researchers Richard Boyatzis and Annie McKee to explore the role of emotional intelligence in leadership. Unveiling neuroscientific links between organizational success or failure and "primal leadership," the authors argue that a leader's emotions are contagious. If a leader resonates energy and enthusiasm, an organization thrives; if a leader spreads negativity and dissonance, it flounders. This breakthrough concept charges leaders with driving emotions in the right direction to have a positive impact on earnings or strategy. Drawing from decades of analysis within world-class organizations, the authors show that resonant leaders - whether CEOs or managers, coaches or politicians - excel not just through skill and smarts, but by connecting with others using EI competencies like empathy and self-awareness. And they employ up to six leadership styles - from visionary to coaching to pacesetting - fluidly interchanging them as the situation demands.The authors identify a proven process through which leaders can learn to: assess, develop, and sustain personal EI competencies over time; inspire and motivate people; cultivate resonant leadership throughout teams and organizations; and, leverage resonance to increase bottom-line performance. The book that no leader in any walk of life can afford to miss, this unforgettable work transforms the art of leadership into the science of results. Daniel Goleman is Codirector of the Consortium for Research on Emotional Intelligence in Organizations at Rutgers University. Richard Boyatzis is Professor and Chair of the Department of Organizational Behavior at the Weatherhead School of Management at Case Western Reserve University. Annie McKee serves on the faculty of the University of Pennsylvania Graduate School of Education and consults to business and organization leaders worldwide.
Unabridged
Keywords: Leadership-Psychological aspects. Management-Psychological aspects. Executive ability. Emotional Intelligence